Die Sendung zu Israel und zu den Völkern im Matthäusevangelium im Lichte seiner narrativen Christologie - Konradt, Matthias (Zeitschrift für Theologie und Kirche, 2004)
The sequence of the divergent mission commands in Mt 10:5f and 28:19 are not to be understood in such a manner that the mission to the nations is the consequence of the rejection Jesus encountered in Israel, but it is to be seen as an integral moment of the narrative concept, in which Matthew gradually unfolds the identity and relevance of Jesus as Son of David and Son of God.